Emissions of N2O and CO2 Following Short-Term Water and N Fertilization Events in Wheat-Based Cropping Systems - Kostyanovsky, Kirill I.; Huggins, David R.; Stockle, Claudio O.; Morrow, Jason G.; Madsen, Isaac J. (Frontiers in Ecology and Evolution, 2019)
Greenhouse gas (GHG) emissions result from short-term perturbations of agricultural systems such as precipitation and fertilization events. We hypothesized those agricultural systems with contrasting management histories may respond differently to application events of water and N fertilizer with respect to GHG emissions. Studies with long-term management histories consisting of no-tillage (NT) and conventional tillage (CT) were coupled with high temporal resolution, automated chambers that monitored N2O and CO2 emissions for 22 hours following treatments. Treatments applied to NT and CT were a) control (no water or N additions), b) simulated precipitation to achieve approximately 80% water-filled pore space, and c) precipitation plus fertilizer additions of 150 kg N ha-1as ammonium nitrate. Emissions of CO2 increased with increase in moisture and temperature and decreased under fertilizer application. Water and nitrogen treatments in CT at the sites with 2 and 12-year history produced N2O fluxes greater than NT by 142% and 68%, respectively. The site with 10-year history of NT produced similar amounts of N2O from CT and NT treatments. The same treatments at the site with 31 yearlong no-till history, despite being one of the lowest among all sites, demonstrated 380% higher N2O fluxes from the NT than CT, which was likely due to higher levels of labile organic matter present in NT treatments. GHG emissions data regressed on measured soil C and N properties, fractionation, and mineralization data showed that N2O flux increased with reduction of acid-hydrolyzable N and increase of NH4-N in soil, which suggested that N2O production in the short-term water and water and N additions events is mostly produced via nitrification process. This indicates that neither the length of no-till treatment nor the fertilizer application rate define the rate of N2O emissions, but the soil N availability controlled by organic matter mineralization rate. The current study shows that the early stages of no-till adoption can result in reduction of N2O spikes during short-term precipitation events similar to some long-term no-till sites.